2,1 vezes 10 elevado a -8 vezes 1.8 vezes 10 elevado a -7
Soluções para a tarefa
Respondido por
1
2,1 * 10^-8 * 1,8 * 10^-7
2,1 * 1,8 * 10^-8 * 10^-7 // 10^-8 * 10^-7 = soma dos expoentes: (-8)+(-7) = -15
2,1 * 1,8 * 10^-15
3,78 * 10^-15 - Notação científica.
2,1 * 1,8 * 10^-8 * 10^-7 // 10^-8 * 10^-7 = soma dos expoentes: (-8)+(-7) = -15
2,1 * 1,8 * 10^-15
3,78 * 10^-15 - Notação científica.
Respondido por
1
Olá!
![2,1\times 10^{-8}\cdot 1,8\times 10^{-7}=2,1\cdot 1,8\times 10^{-8+(-7)} = \\ \\ =
3,78\times 10^{-15}. 2,1\times 10^{-8}\cdot 1,8\times 10^{-7}=2,1\cdot 1,8\times 10^{-8+(-7)} = \\ \\ =
3,78\times 10^{-15}.](https://tex.z-dn.net/?f=2%2C1%5Ctimes+10%5E%7B-8%7D%5Ccdot+1%2C8%5Ctimes+10%5E%7B-7%7D%3D2%2C1%5Ccdot+1%2C8%5Ctimes+10%5E%7B-8%2B%28-7%29%7D+%3D+%5C%5C+%5C%5C+%3D+%0A3%2C78%5Ctimes+10%5E%7B-15%7D.)
Bons estudos!
Bons estudos!
G4Br13L2334:
nao ficou muito claro
Perguntas interessantes
Artes,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás
Física,
1 ano atrás